Contemporary Muamalah And Hifz Al-Mal: A Study On The Digitalization Of The Financial System At Al-Amien Prenduan Islamic Boarding School - M. Haris Hidayatulloh; Bhismoadi Tri Wahyu Faizal; Akhmad Farid Mawardi Sufyan; Hanuri Firman Erentama (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Introduction: The advancement of financial technology has transformed the landscape of financial management, compelling Islamic boarding schools (pesantren) to adopt reactive and responsive policies. This study aims to examine the digitalization of the financial system at Al-Amien Prenduan Islamic Boarding School, encompassing the planning and formulation of digital system transformation, its implementation and development, as well as the manner in which the institution integrates such transformation with the principles of Ḥifẓ al-Māl. Methods: This study employs a qualitative-empirical method, addressing the research focus through three stages of data analysis, namely data reduction, data presentation, and conclusion. Results: The findings indicate that the transformation of the student payment system from manual to digital was systematically planned, practically implemented to resolve various financial issues grounded in the principles of Ḥifẓ al-Māl as part of Maqāṣid al-Sharīʿah, and evaluated to achieve a system with optimal performance in attaining maṣlaḥah Conclusion and suggestion: The integration of the principles of Ḥifẓ al-Māl into the digital payment system has proven to be an effective instrument and solution in resolving financial problems, thereby creating a transparent and accountable financial system.